MONITORING DAN EVALUASI KETERSEDIAAN DAN PENGGUNAAN OBAT DI INSTALASI FARMASI RSUD SULTAN SULAIMAN KABUPATEN SERDANG BEDAGAI TAHUN 2020 - Wirda, Sri (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
Monitoring is activity to carefully observe a situation or condition, including certain behaviors or activities, with the aim that all input data or information is obtained from the results of observations. Evaluation is act of making a decision to assess object, situation, event or activity that is being observed. The background of the research at Sultan Sulaiman Hospital, Kabupaten Serdang Bedagai. The absence of good monitoring and evaluation process on the availability of drugs, plus non-compliance of specialists in prescribing drugs according to the formulary contents. Research objective was to determine the efforts, benefits, constraints and follow-up in processing human resources, funds, facilities and methods after monitoring and evaluating drug availability and drug use at Sultan Sulaiman Hospital, Kabupaten Serdang Bedagai. The method this research is qualitative. Effort made that each sector makes a unit requirement plan (RKBU) so that head of the planning and development sector can summarize all the RKBU and make it an OPD work plan. The way is done to make use of by carrying out the correct planning process and using management principles. Then in terms of funds, the means and methods must be carried out effectively and efficiently and efficiently. The obstacles faced are limited district government budget and the low commitment of the leadership in building health facilities and infrastructure. The follow up to determine the working hours of specialist doctors with Regulation number 53 concerning civil servant discipline and make rules on compliance using hospital formularies in fulfillment of medicines for patients.